Bond and topography evaluation of a Y-TZP ceramic with a superficial low-fusing porcelain glass layer after different hydrofluoric acid etching protocols - SimÕes, Arthur Chaves (2018)
AbstractIntroductionDespite being one of the most studied ceramics today, zirconia still does not have a well-defined adhesion protocol.ObjectiveEvaluate the influence of different etching times and hydrofluoric acid (HF) concentrations on the zirconia surface and bond strength between a vitrified Y-TZP ceramic and a resin cement.Materials and methodThe zirconia surface treatments were: sandblasting with silica-coated alumina (Co); glaze application + 5% HF etching for 5s (G5-5s), 10s (G5-10s) or 20s (G5-20s); glaze application + 10% HF etching for 5s (G10-5s), 10 (G10-10s) or 20s (G10-20s) . Then, cement cylinders (3.3 × 3.3 mm) were built up for shear bond test on all specimens. The specimens were subjected to 6000 thermal cycling before the test. Fractures were analyzed by stereomicroscope. Data were statistically analyzed by Kruskal-Wallis and Dunn statistical tests (5%). Extra samples of each group were made to obtain profilometry and scanning electron microscopy (SEM).ResultZirconia-cement bond strength was affected by the ceramic surface treatments (p = 0.001). G10-5s (2.71 MPa) recorded the highest bond strength values, followed by the Co (2.05 MPa) while G5 groups had the lowest bond value. Adhesive failure of the samples predominated. The image analysis revealed G5 groups seem to have a lower roughness when compared to groups treated by 10% HF. The creation of pores in the low-fusing porcelain glass layer surface occurred only when 10% HF was used.ConclusionThe low-fusing porcelain glass layer application was able to overcome the sandblasting and obtain a greater adhesive bond to the resinous cement, however, only when 10% HF was used for an interval of 5 seconds.